Education of the Post-Industrial Era: Setting on Person and Intelligence - O. K. Krokinskaya (Высшее образование в России)
The article discusses theoretical background and empirical premises for supplementing the goals of education with orientation to individual actor as the “assemblage point” of the educational result in a constantly changing reality. The article has an interdisciplinary modus, its theoretical basis is the D. Bell’s concepts of the post-industrial society, the “liquid modernity” of Z. Bauman and the idea of C.S. Dweck about the ability of personality’s sets “plants for growth” or “for granted” to influence intellect and achievement of goals. The work proceeds from the understanding of the fact that the “spreading” state of education is due to the specifics of the transition to some post-state of the society that is not yet clear. It is characterized by the fundamental ambiguity of circumstances and tendencies when centralized management of complex systems is difficult or erroneous, and this makes it necessary to reduce the level of decision making to self-organizing local social forms, giving them greater autonomy, in this case – to an individual and his autonomy. However, in our culture we have a lack of confidence to the individual and his ability to make wise choices, as well as, wittingly or unwittingly, reduce the setting for growth and primacy. But if students are offered well-organized research practices instead of imitations of scientific work, then they form the true key competencies necessary for modern society – a willingness to be in search, continuously learn and create new solutions for new tasks, contribute to the development of good conceptual language, cooperation in group work, courage in posing problems, readiness to work with complex problems. The article presents a kind of a case analysis of such work. The article also poses the problem of exploiting the cognitive status and well-being of teachers in super-formalized labor practices.